A solvent-free process to design low density polyhydroxyalkanoate. Issue 2 (May 2023) - De Carvalho, Eva; Chebil, Mohamed; Fay, Fabienne; Renard, Estelle; Langlois, Valérie
The polyhydroxyalkanoates (PHAs) are biobased, biocompatible and biodegradable polyesters. To enhance their biodegradability and flexibility, we develop low density PHAs by an emulsion-templated method without organic solvent. Polycaprolactone (PCL) and castor oil are required to improve the flexibility and to generate the porosity, respectively. To overcome the well-known lack of compatibility between PHA and PCL, pluronic is introduced to improve the miscibility of these polyesters The densities of native PHA and PCL are 1.2 g.cm −3 and the densities decreased to 0.49 g.cm −3 in presence of castor oil (40 wt%). Different PHAs were studied: polyhydroxybutyrate (PHB), polyhydroxybutyrate-co-hydroxyvalerate (PHBHV) and polyhydroxybutyrate-co-hydroxyhexanoate (PHBHHx). The porous PHBHHx based material showed the best colonization by Pseudomonas, followed by the PHBHV and PHB. This colonization only occurred in the surface and no bacterial diffusion was observed inside the material. The biodegradability study in presence of lipase showed that after 8 days, the weight losses are, respectively, 20% and 75% when the densities decreased from 0.82 g.cm −3 to 0.49 g.cm −3 . These results showed the importance of the porosity on the biodegradation of PHAs. Graphical Abstract